2021
DOI: 10.1002/bit.27855
|View full text |Cite
|
Sign up to set email alerts
|

On‐chip determination of tissue‐specific metastatic potential of breast cancer cells

Abstract: Metastasis is one of the major obstacles for breast cancer patients. Limitations of current models demand the development of custom platforms to predict metastatic potential and homing choices of cancer cells. Here, two organ‐on‐chip platforms, invasion/chemotaxis (IC‐chip) and extravasation (EX‐chip) were used for the quantitative assessment of invasion and extravasation towards specific tissues. Lung, liver and breast microenvironments were simulated in the chips using tissue‐specific cells embedded in matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…4 ), we investigated the effect of knock-down in invasive characteristics of this MIBC cell line. To test the invasion capability of T24 cells for the knock-downs, we used IC-CHIP assay, which enables the detection of invasion ability through matrigel across different microenvironment 55 57 in three conditions: Positive control (10% FBS), negative control (0% FBS) and muscle microenvironment (Fig. 6a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ), we investigated the effect of knock-down in invasive characteristics of this MIBC cell line. To test the invasion capability of T24 cells for the knock-downs, we used IC-CHIP assay, which enables the detection of invasion ability through matrigel across different microenvironment 55 57 in three conditions: Positive control (10% FBS), negative control (0% FBS) and muscle microenvironment (Fig. 6a ).…”
Section: Resultsmentioning
confidence: 99%
“…While drawing boxplots, outlier data were excluded from the graphs using “geom_boxplot (outlier.shape = NA)” function in ggplot2 package 98 , source data includes outlier data too. The invasion capacity of the cells was determined through the normalization of datasets to day 0 55 for T24 and day 1 for 5637 cells. Three independent experiments were performed for each dataset.…”
Section: Methodsmentioning
confidence: 99%
“…4), we investigated the effect of knock-down in invasive characteristics of this MIBC cell line. To test the invasion capability of T24 cells for the knock-downs, we used IC-CHIP assay, which enables the detection of invasion ability through matrigel across different microenvironment 36, 37, 86 in three conditions: Positive control (10% FBS), negative control (0% FBS) and muscle microenvironment (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of images was performed by Python programming and R Studio as previously described 36 . The invasion capacity of the cells was determined through normalization of datasets to day 0 37 for T24 and to day 1 for 5637 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Firatligil-Yildirir et al utilized organ-on-a-chip platforms to investigate the invasion/chemotaxis behavior of TNBC cells (Figure 5i-l). 71 The modular LOC platform allows the generation of different homing sites including lung, liver and breast microenvironments simulated in a matrigel matrix. It was shown that MDA-MB-231 TNBC cells preferred to invade the lung site compared to the liver or breast microenvironments.…”
Section: Modelling Cell Migration and Invasionmentioning
confidence: 99%